Implementation and Optimization Strategy of SG-CCTV Inspection of CPR1000 Nuclear Power Station. Issue 1 (October 2020) - Li, Tian; Li, Cheng; Chen, Yanhui; Xue, Donglin
Abstract: The video inspection for primary side water chamber of the steam generator (For short: SG-CCTV inspection) was an important item of nuclear island in-service inspection. According to the structure of primary side water chamber and SG-CCTV inspection equipment, implementation and management strategies of SG-CCTV inspection were introduced. From the perspective of equipment and item management, the problems during SG-CCTV implementation process were analysed. To solve those problems, suggestions for equipment improvement and item optimization management were put forward.